Feminism and the Horrors of Toxic Masculinity in Pedro Almodóvar's The Skin I Live In (2011). Issue 3 (23rd March 2023) - Nagy, Mason
This article analyzes the Spanish horror film The Skin I Live In (TSILI) from a feminist perspective. Different feminist theories such as the male gaze, toxic masculinity, and the Final Girl are used to explore how TSILI criticizes heteronormative masculinity. By comparing Almodóvar's film to other horror classics such as Psycho and Halloween, I discuss how TSILI offers a unique and modernist depiction of gender within horror.